TANGGUNGJAWAB WERDA NOTARIS TERHADAP AKTA YANG DIBUATNYA - HERIANTO SINAGA (PREMISE LAW JURNAL, 2015)
Notary public officials prosecuted as responsible for the deed he had done, even though the notary protocol has been submitted or transferred to the storage protocol notary. In accordance with the provisions of Article 65 UUJN, nursing notary still be held accountable for every deed he made. After the end of his tenure, there is no provision in the UUJN which describes the legal protection of nursing notary, because UUJN only regulate matters relating to active notaries. The legal position of notary protocol switch to a notary that replaces the notary who has ended his term of office, or to the Regional Supervisory Council, as provided for in Article 63 paragraph (5) UUJN. Keywords: nursing notary, accountability, deed